Phenotypic effects of the dwarfing gene Rht-17 in spring durum wheat under two climatic conditions - A. G. Chernook; P. Yu. Kroupin; L. A. Bespalova; V. V. Panchenko; V. Ya. Kovtunenko; M. S. Bazhenov; L. A. Nazarova; G. I. Karlov; A. Yu. Kroupina; M. G. Divashuk (Вавиловский журнал генетики и селекции)
Alleles of the genes, conferring a dwarfing phenotype, play a crucial role in wheat breeding, as they not only reduce plant height, ensuring their resistance to lodging, but also have a number of positive and negative pleiotropic effects on plant productivity. Durum wheat carries only two subgenomes (A and B), which limits the use of the D-subgenome genes and requires the expansion of the arsenal of dwarfing alleles and the study of their effects on height and agronomically important traits. We studied the effect of the gibberellin-insensitive allele Rht-B1p in the B2F2:3 families, developed by crossing Chris Mutant /#517//LD222 in a field experiment in Moscow and Krasnodar. In our experiments, plants homozygous for Rht-B1p were shorter than those homozygous for the wild-type allele Rht-B1a by 36.3 cm (40 %) in Moscow and 49.5 cm (48 %) in Krasnodar. In the field experiment in Krasnodar, each plant with Rht-B1p had one less internode than any plant with Rht-B1a, which additionally contributed to the decrease in plant height. Grain weight per main spike was lower in plants with Rht-B1p than in plants with Rht-B1a by 12 % in Moscow and by 23 % in Krasnodar due to a decrease in 1000 grain weight in both regions of the field experiment. The number of grains per main spike in plants with Rht-B1p was higher in comparison to that with Rht-B1a by 6.5 % in Moscow due to an increase in spikelet number per main spike and by 11 % in Krasnodar due to an increase in grain number per spikelet. The onset of heading in plants with Rht-B1p in comparison with the plants with the wild-type allele Rht-B1a was 7 days later in Krasnodar. The possibility and prospects for the use of Rht-B1p in the breeding of durum wheat are discussed.